Case report of benign familial fleck retina - Nipun Bagrecha; M Prabhushanker; G Geetha; Nikulaa Parachuri (TNOA Journal of Ophthalmic Science and Research, 2022)
Benign familial fleck Retina is a rare inherited retinal disease first reported by Sabel Aish and Dajani in 1980. It is an autosomal recessive condition associated with a distinctive retinal appearance with no apparent visual or electrophysiological deficits. Fundus photography, autofluorescence and enhanced depth optical coherence tomography B-scan imaging modalities aid in the diagnosis. We present a case report of a 19-year-old female diagnosed with benign familial fleck retina which belongs to a heterogeneous group of flecked retina syndromes, and should be considered in patients with yellowish-white retinal lesions sparing the macula.